2018
DOI: 10.1007/s00213-018-4942-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anxiogenic drugs on the emission of 22- and 50-kHz ultrasonic vocalizations in adult rats

Abstract: Anxiogenic drugs, as a class, did not uniformly alter the 50-kHz call rate or subtype profile. Amphetamine-induced effects on 50-kHz call rate and profile do not reflect anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Other studies have found more selective effects on specific vocalizations. Two separate studies showed that injection of amphetamine causes a selective increase in trills and a decrease in 50 kHz flat calls [ 3 , 53 ]. In sum, amphetamine induces trills and possibly other frequency-modulated calls.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found more selective effects on specific vocalizations. Two separate studies showed that injection of amphetamine causes a selective increase in trills and a decrease in 50 kHz flat calls [ 3 , 53 ]. In sum, amphetamine induces trills and possibly other frequency-modulated calls.…”
Section: Discussionmentioning
confidence: 99%
“…Place-preference behavior was reported after amphetamine injections that induced emission of 50 kHz vocalizations [ 344 ], confirming its hedonic nature. Despite suggestions that 50 kHz calls might be an (anxious) indicator of negative reinforcement learning [ 351 ], a recent pharmacological study has confirmed that emission of amphetamine-induced 50 kHz vocalizations reflect a hedonic state that is resistant to anxiogenic agents and, therefore, does not reflect anxiety [ 352 ]. Moreover, rats can also learn self-injection of amphetamine directly into the shell of the nucleus accumbens, further indicating hedonic nature of this activation [ 353 ].…”
Section: Vocalization As Expression Of Emotional Arousalmentioning
confidence: 99%
“…Possible mood-modifying effects of nornicotine have apparently not been studied in human subjects, whereas cotinine appears not to improve mood and may possibly be mildly anxiogenic (Benowitz et al 1983;Hatsukami et al 1998;Keenan et al 1994). Since drug-induced anxiety does not appear to produce a consistent change in USV emission (Willadsen et al 2018), cotinine would be expected not to affect USV emission, whereas nornicotine would mimic nicotine, albeit less potently, based its nicotine-like activity in other in vitro and behavioral assays (see above). In the present study, we also analyzed the rate of 50-kHz call emission, predicting that since our rats had a history of nicotine exposure, this drug would likely promote 50-kHz calling (Swalve et al 2016), potentially providing an additional measure with which to assess drug-drug interactions.…”
Section: Introductionmentioning
confidence: 99%